Thalamic Lesions: A Radiological Review. (2nd July 2014) - Renard, Dimitri; Castelnovo, Giovanni; Campello, Chantal; Bouly, Stephane; Le Floch, Anne; Thouvenot, Eric; Waconge, Anne; Taieb, Guillaume
Abstract : Background . Thalamic lesions are seen in a multitude of disorders including vascular diseases, metabolic disorders, inflammatory diseases, trauma, tumours, and infections. In some diseases, thalamic involvement is typical and sometimes isolated, while in other diseases thalamic lesions are observed only occasionally (often in the presence of other typical extrathalamic lesions). Summary . In this review, we will mainly discuss the MRI characteristics of thalamic lesions. Identification of the origin of the thalamic lesion depends on the exact localisation inside the thalamus, the presence of extrathalamic lesions, the signal changes on different MRI sequences, the evolution of the radiological abnormalities over time, the history and clinical state of the patient, and other radiological and nonradiological examinations.